Gambaran Kepuasan Pernikahan pada Istri Pertama yang Dipoligami (Studi Pernikahan di Bawah 10 Tahun) - Yanissya Purnomo; Agustini (Universitas Mercu Buana, 2026)
This study investigates marital satisfaction among first wives in polygamous marriages lasting less than 10 years. Using a phenomenological qualitative approach, four first wives married under 10 years were interviewed in-depth. The analysis focused on communication, commitment, emotional closeness, role distribution, and economic conditions. Findings reveal that before polygamy, marriages were relatively stable with clear communication and expectations of long-term unity. After polygamy commenced, all participants reported decreased marital satisfaction, characterized by reduced emotional intimacy, trust, communication, and altered commitment meanings. Key factors contributing to this decline included the husband's lack of transparency, changed time and attention allocation, imbalanced domestic roles, and economic instability from supporting a second family. The subjects went through emotional stages of shock, rage, and disappointment. While the presence of children became the primary reason for all subjects to stay, religious values and social support became the primary reinforcing factors for NV, FT, and YT in maintaining their relationships. In order to minimize changes in marital quality and long-term emotional impacts, psychological preparedness, transparency, relational fairness, and psychosocial support are necessary. This study demonstrates that polygamy in marriage phases under ten years has the potential to disrupt previously established relational stability